2006
DOI: 10.1002/bies.20473
|View full text |Cite
|
Sign up to set email alerts
|

Extraneuronal roles of cyclin‐dependent kinase 5

Abstract: Cyclin-dependent kinase 5 (Cdk5) is recognized as an essential molecule in the brain, where it regulates several neuronal activities, including cytoskeletal remodeling and synaptic transmission. While activity of Cdk5 has primarily been associated with neurons, there are now substantial data indicating that the kinase's activity and function are more general. An increasing body of evidence has established Cdk5 kinase activity, the presence of the Cdk5 activators, p35 and p39, and Cdk5 functions in non-neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 95 publications
3
97
0
Order By: Relevance
“…This implies that CDK5-p35 activity is required for optimum levels of GTP-induced secretion from primary (azurophil) and secondary (specific) granules [37,38]. We found no change in levels of CD11b localization (which resides in secondary granules) upon treatment with R-roscovitine when compared with control.…”
Section: Discussionmentioning
confidence: 59%
“…This implies that CDK5-p35 activity is required for optimum levels of GTP-induced secretion from primary (azurophil) and secondary (specific) granules [37,38]. We found no change in levels of CD11b localization (which resides in secondary granules) upon treatment with R-roscovitine when compared with control.…”
Section: Discussionmentioning
confidence: 59%
“…Initially, CDK5 was implied in the regulation of neuronal functions including cytoskeletal remodeling and synaptic transmissions. Recently, an increasing array of evidence established its function and presence in nonneuronal cells as well (24). CDK5 has been shown as a regulator of the association between GLUT4 and the synaptotagmin homolog, E-syt1, to modulate glucose transport in adipocytes upon insulin stimulation (25).…”
Section: Discussionmentioning
confidence: 99%
“…3B). Separate phosphorylation studies of the GSTfusions C2 (1)(2) , C2 (3) , and C2 (4)(5) revealed that only the C2 (1.2) construct was phosphorylated (Fig. 3C).…”
Section: E-syt1 Expression Is Induced During Adipocyte Differentiatiomentioning
confidence: 98%
“…In noncycling cells, Cdk5 phosphorylates multiple substrates to control such diverse phenomena as cell signaling, adhesion and motility, cytoskeletal organization, protein trafficking, and membrane fusion and dynamic organization (2). The membrane-bound Cdk5 effectors, p35/p39, direct and activate the kinase to specific membrane targets via mechanisms that are not yet well understood (3)(4)(5)(6).…”
mentioning
confidence: 99%